Heterogeneity in Cardiovascular Disease Risk Factors Among Latino Immigrant Subgroups: Evidence From the 2010 to 2018 National Health Interview Survey - Sabrina Elias; Ruth‐Alma Turkson‐Ocran; Binu Koirala; Samuel Byiringiro; Diana Baptiste; Cheryl R. Himmelfarb; Yvonne Commodore‐Mensah (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2023)
Background The Latino population is a growing and diverse share of the US population. Previous studies have examined Latino immigrants as a homogenous group. The authors hypothesized that there would be heterogeneity in cardiovascular disease risk factors among Latino immigrant subgroups (from Mexico, Puerto Rico, Cuba, Dominican Republic, Central America, or South America) compared with non‐Latino White adults. Methods and Results A cross‐sectional analysis of the 2010 to 2018 National Health Interview Survey (NHIS) among 548 739 individuals was performed. Generalized linear models with Poisson distribution were fitted to compare the prevalence of self‐reported hypertension, overweight/obesity, diabetes, high cholesterol, physical inactivity, and current smoking, adjusting for known confounders. The authors included 474 968 non‐Latino White adults and 73 771 Latino immigrants from Mexico (59%), Puerto Rico (7%), Cuba (6%), Dominican Republic (5%), Central America (15%), and South America (9%). Compared with White adults, Mexican immigrants had the highest prevalence of overweight/obesity (prevalence ratio [PR], 1.17 [95% CI, 1.15–1.19]); Puerto Rican individuals had the highest prevalence of diabetes (PR, 1.63 [95% CI, 1.45–1.83]); individuals from Central America had the highest prevalence of high cholesterol (PR, 1.16 [95% CI, 1.04–1.28]); and individuals from the Dominican Republic had the highest prevalence of physical inactivity (PR, 1.25 [95% CI, 1.18–1.32]). All Latino immigrant subgroups were less likely to be smokers than White adults. Conclusions The authors observed advantages and disparities in cardiovascular disease risk factors among Latino immigrants. Aggregating data on Latino individuals may mask differences in cardiovascular disease risk and hinder efforts to reduce health disparities in this population. Study findings provide Latino group–specific actionable information and targets for improving cardiovascular health.